2018
DOI: 10.1016/j.chest.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice and Infrastructure Review of Fecal Microbiota Transplantation for Clostridium difficile Infection

Abstract: A substantial proportion of Clostridium difficile infection (CDI) cases recur after completion of antibiotic therapy, and antibiotic cure rates diminish with each recurrence of CDI. Fecal microbiota transplantation (FMT) is an effective therapy for recurrent FMT, which otherwise requires prolonged or indefinite antibiotic treatment. FMT is performed by introducing the fecal microbial community obtained from a healthy donor or pool of donors into the stomach, small intestine, or colon of a patient with CDI. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 132 publications
(201 reference statements)
0
41
0
2
Order By: Relevance
“…The present case report demonstrated that C. difficile antigen and toxin A&B genes and proteins turned into negative, and stool consistency and frequency and faecal blood and mucus became normal after oral FMT in a dog with large bowel diarrhoea. Successful clinical outcomes of FMT for recurrent CDI have been reported in humans [5][6][7] and a marmoset [3]. These findings collectively suggest that correction of gut microbiota with FMT can be a useful treatment option for C. difficile-associated diarrhoea across animal species.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The present case report demonstrated that C. difficile antigen and toxin A&B genes and proteins turned into negative, and stool consistency and frequency and faecal blood and mucus became normal after oral FMT in a dog with large bowel diarrhoea. Successful clinical outcomes of FMT for recurrent CDI have been reported in humans [5][6][7] and a marmoset [3]. These findings collectively suggest that correction of gut microbiota with FMT can be a useful treatment option for C. difficile-associated diarrhoea across animal species.…”
Section: Discussionmentioning
confidence: 74%
“…The pathogenesis of CDI is well established in humans, and involves toxin production by colonic C. difficile and depletion of non-C. difficile colonic microbiota [5]. However, it is still controversial whether C. difficile plays a pathological role in the development of diarrhoea in dogs [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Finally, fecal transplantation for CDI relapse has been shown to be an effective, nonantibiotic therapy, although its use is limited in the US. 22,23 …”
Section: Introductionmentioning
confidence: 99%